Domestic Violence, Gun Possession, and the Importance of Context - Oliver, Wesley M (2015)
Context is everything. A federal law prohibits those convicted of committing an act of domestic violence from possessing weapons. 1 This term, the U.S. Supreme Court decided that this statute would apply even to those convicted of crimes that did not necessarily involve violent acts.2 This conclusion strains the ordinary meaning of language, but is quite consistent with a long tradition in criminal cases that favors a pro-government interpretation of a statute when the public welfare is at stake. And domestic violence, Justice Sotomayor stressed in her opinion, has reached epidemic levels, prompting Congress to get guns out of the hands of abusers.